Pengaruh Pelatihan Medicine Ball Sit Up Throw Terhadap Kekuatan Otot Lengan dan Otot Punggung Pada Siswa Putra kelas VII SMP Negeri 4 Bolo: Efektivitas Latihan Medicine Ball Sit Up Throw Terhadap Kekuatan Otot Lengan dan Punggung Pada Siswa Sekolah Menengah Pertama - Hidayat, Taufiq (INSPIREE: Indonesian Sport Innovation Review, 2021)
The  purpose  of  the study. To determine the effect of medicine ball sit-up throw training on arm and back muscle strength. Materials  and  methods. With the Randomized Control Group Pretest-Posttest Design, this sort of study is a true experiment. In this study, 44 male students made up the sample. The arm muscle strength variable was measured using a 60 second push-up test, while the back muscle strength variable was measured using a back and leg dynamometer test instrument. Results. Data were analyzed by independent t test at a significantly smaller level (α) 0.05 with SPSS 16.0 application. Based on the results of independent t-test obtained results; (1) arm muscle strength variable with a significant value of 0.000. (2) Back muscle strength variable with a significant value of 0.010. The calculated significant value is smaller than the value of (0.05) thus the research hypothesis of medicine ball sit up throw training affects the strength of the arm and back muscles "accepted". Conclusions. Thus, it was concluded that medicine ball sit up throw training had a significant effect on arm and back muscle strength in male students. It is recommended for sports teachers, coaches, coaches, and athletes to use arm muscle strength and back muscle strength.